2017
DOI: 10.1007/s00438-017-1381-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of genetic loci in estimated glomerular filtration rate and type 2 diabetes using a pleiotropic cFDR method

Abstract: Genome-wide association studies (GWAS) have been shown to have the potential of explaining more of the “missing heritability” of complex human phenotypes by improving statistical approaches. Here, we applied a genetic-pleiotropy-informed conditional false discovery rate (cFDR) to capture additional polygenic effects associated with estimated glomerular filtration rate (creatinine) (eGFRcrea) and type 2 diabetes (T2D). The cFDR analysis improves the identification of pleiotropic variants by incorporating potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…We previously demonstrated that NHA2 resides in endosomes of β-cells and is critical for insulin secretion 10,11 . In support of this finding, a single-nucleotide polymorphism in the NHA2 gene was recently discovered in a genome-wide association study as a new locus associated with type 2 diabetes in humans 12 . In the rodent kidney, NHA2 was previously detected in the distal nephron, including the distal convoluted tubules (DCT), but its quantitative expression pattern along the nephron remains unknown 13,14 .…”
Section: Translational Stateentmentioning
confidence: 78%
“…We previously demonstrated that NHA2 resides in endosomes of β-cells and is critical for insulin secretion 10,11 . In support of this finding, a single-nucleotide polymorphism in the NHA2 gene was recently discovered in a genome-wide association study as a new locus associated with type 2 diabetes in humans 12 . In the rodent kidney, NHA2 was previously detected in the distal nephron, including the distal convoluted tubules (DCT), but its quantitative expression pattern along the nephron remains unknown 13,14 .…”
Section: Translational Stateentmentioning
confidence: 78%
“…Second, a recent genome-wide association study (GWAS) of renal function identified NHA2 as a genetic risk locus for estimated glomerular filtration rate by serum creatinine. GFR, which shows heritability in the range of 36-75%, is commonly used to monitor kidney function decline in PKD (75). Third, NHA2 expression is predominant in the distal nephron where sodium reabsorption is under hormonal and dietary control and, consistent with the induction of renal NHA2 expression by a high salt diet in mouse (15,19).…”
Section: Discussionmentioning
confidence: 90%
“…Glomerular filtration rate, which shows heritability in the range of 36–75%, is commonly used to monitor kidney function decline in PKD (Schrier, ; Liu et al . ). Third, NHA2 expression is predominant in the distal nephron where sodium reabsorption is under hormonal and dietary control, consistent with the induction of renal NHA2 expression by a high salt diet in mouse (Fuster et al .…”
Section: Discussionmentioning
confidence: 97%